Comparing adults and adolescents regarding the scope insensitivity of value curves: A functional measurement approach (2016)
The curvature of the value/utility function has been understood, since D. Bernouilli, as the expression of an attitude towards risk. This perspectivewas kept in such influential theories of judgment and decision as Prospect Theory, in both its original and cumulative versions (Kahneman & Tversky, 1979; Tversky & Kahneman, 1992). More recently, dualprocess interpretations of the value function as a mix of affect and deliberation (Hsee & Rottenstreich, 2004) have proposed that function curvature reflects the operation of affect-based evaluations via an affective focus coefficient indexed by “α” (varying between 0 and 1) in the equation v = A αS 1-α (with “v” the subjective value, “A” the intensity of the affective response, and “S” the scope of the stimuli). According to this view, evaluating more hedonic targets results in more curved (scopeinsensitive) functions than evaluating instrumental/utilitarian targets, and more affect-oriented subjects exhibit more pronounced curvatures (lower 1α) than deliberation-oriented subjects. These predictions are evaluated in this study and additionally used for an exploratory evaluation of Reyna and Farley’s (2006, 2007) proposal that analytical processing and gist/affect-based processing predominate, respectively, in adolescents’ and in adults’ judgment and decision making. Information Integration Theory was used to establish a model allowing for the functional measurement of subjective value at the (ratio) level required for comparing curvature parameters and computing Loss Aversion coefficients. The outcomes partially favored the prediction of larger curvatures (lower 1- α) and larger loss aversion in more hedonic tasks. However, they did not support the prediction of more scope insensitivity and larger values of loss aversion in adults than in adolescents. As the main suggested difference between adults and adolescents, individual differences in risk attitude appeared to be less polarized towards loss aversion among adolescents in more hedonic tasks.